An efficient method for isolation of plasmid DNA from methylotrophic bacteria - Brenner, V; Holubová, I; Hubácek, J (Folia microbiologica, 1990)
A method, suitable for the isolation of closed circular plasmid DNA from methylotrophic bacteria is described. Improvement of cell lysis was achieved by butanol extraction of cells before application of the lytic agent. Using this method, cryptic plasmids of 7.8, 14, 36 and 200 kb were purified from soil-isolated methylotrophs.
Keywords: Methylococcaceae; Plasmids; kruhová DNA; půdní mikrobiologie; DNA, Bacterial; Soil Microbiology; oxidace-redukce; methanol; DNA bakterií; plazmidy; Methanol; Oxidation-Reduction; DNA, Circular